2020
DOI: 10.1371/journal.pone.0226480
|View full text |Cite
|
Sign up to set email alerts
|

Performance of cardiopulmonary exercise testing for the prediction of post-operative complications in non cardiopulmonary surgery: A systematic review

Abstract: Introduction Cardiopulmonary exercise testing (CPET) is widely used within the United Kingdom for preoperative risk stratification. Despite this, CPET's performance in predicting adverse events has not been systematically evaluated within the framework of classifier performance. Methods After prospective registration on PROSPERO (CRD42018095508) we systematically identified studies where CPET was used to aid in the prognostication of mortality, cardiorespiratory complications, and unplanned intensive care unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 55 publications
1
32
0
1
Order By: Relevance
“…While there are few systematic reviews indicating a positive association between superior preoperative CPET values and absence of postoperative complications, others reported no significant association. 5 , 7 , 8 , 10 , 11 This is somewhat in line with the results of the current review. Our meta-analysis showed that superior preoperative CPET values are significantly associated with the absence of most postoperative complications.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…While there are few systematic reviews indicating a positive association between superior preoperative CPET values and absence of postoperative complications, others reported no significant association. 5 , 7 , 8 , 10 , 11 This is somewhat in line with the results of the current review. Our meta-analysis showed that superior preoperative CPET values are significantly associated with the absence of most postoperative complications.…”
Section: Discussionsupporting
confidence: 92%
“…Previous systematic reviews included a smaller number of studies (ranging from 7–37), investigated postoperative complications as the main outcome measure, and included either a specific cancer population undergoing surgery (e.g., lung, esophageal), or mixed populations undergoing surgery for cancer and/or noncancer related conditions. 5 , 7 11 Meta-analysis was attempted in only half of the previous published systematic reviews. Therefore, the mixed results encountered between the current review and previous reviews may be because the inclusion and exclusion criterion were different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Keller et al suggested that BP overresponse in CPET might be a diagnostic tool for identifying high-risk groups of hypertension [ 21 ]. Besides, CPET can be used as a tool for preoperative risk stratification of patients (not limited to cardiopulmonary surgery) to predict postoperative adverse outcomes [ 22 , 23 ]. Currently, one of the most impressive advances is that the integration of CPET and other tests has been introduced to diagnose several diseases [ 24 ].…”
Section: Related Workmentioning
confidence: 99%